Clinical Characteristics and Outcomes of Short-term Repeat Corneal Transplantation. (19th May 2022) - Chen, Xiunian; Li, Ting; Qi, Xiaolin; Shi, Weiyun; Gao, Hua
ABSTRACT: Purpose: To explore the primary indications, direct causes and graft survival of short-term repeat keratoplasty. Methods: An analytical cross-sectional study. Results: The primary indications for keratoplasty were infectious keratitis (67.9%) and immune keratopathy (12.8%). The direct causes of graft failure were infectious ulcer (43.6%) and recurrence (30.8%). Pre-operative hypopyon (P = 0.017, HR = 1.757) and use of decellularized porcine corneas as grafts (P = 0.005, HR = 2.690) were independent risk factors for graft failure. The Kaplan–Meier analysis revealed that the 1-year survival rate of 88 repeat grafts was 85.2%, and the 5-year survival rate was 79.2%. The survival rates of the repeat grafts were significantly higher than those of the first grafts (P < 0.001). Conclusion: Infectious keratitis is the most common indication of short-term graft failure and is often failed by infectious ulcer and keratitis recurrence. While the decellularized porcine cornea is a promising application in developing countries, certain difficulties, such as graft melting, remain unresolved.